Which quadratic function has its vertex at (-2,7) and opens down?

Answers

Answer 1
Answer: The \ vertex \ form \ of \ the \ function \ is: \n \ny = a(x - h)^2 + k\n \nvertex = \ is \ the point \n \n(h, k) = (-2,7)\n\nh=-2\nk=7

y=a(x-(-2))^(2) +7\n\ny=a(x+2)^(2) +7 \n\n opens \ up \ down \ for : \ a < 0 \n For \ instance, \ letting \ a = -1 \ gives \ this \ parabola: \n\ny= -(x+2)^(2) +7




Answer 2
Answer: The\ vertex\ form:y=a(x-h)^2+k\n\nvertex(h;\ k)\to(-2;\ 7)\n\no pens\ down\ then\ a < 0\n\nAnswer:y=a(x+2)^2+7\ where\ a < 0.

Related Questions

A spinner with 10 equally sized slices has 2 red slices, 4 yellow slices, and 4 blue slices. The dial is spun and stops on a slice at random. What is the probability that the dial stops on a red slice?
How to solve this problem
Write the equation of line perpendicular to y = 4 that passes through (5, 2).
Write an equation in point slope form of the line passes through the point (0,2) and has a slope of m=4
HELPP PLEASEEEEEE!!!!!

If x2=y3, what is the value of z does x3z=y9?

Answers

If x² = y³ , for what value of z doesx^(3z) =  Y^(9)  ?

Answer:

z= 2

Step-by-step explanation:

To solve the question given, we will follow the steps below;

X^(3z) =  Y^(9)   -----------------------------------------------------------------(1)

but   applying the law of indices mᵃᵇ = (mᵃ)ᵇ

then

Y^(9)  = (Y^(3))^(3)

replace  Y^(9)  by  (Y^(3))^(3)  in equation (1)

X^(3z) =  Y^(9)

X^(3z) =   (Y^(3))^(3)   --------------------------------------------------------------------(2)

but  from the question x² = y³

replace y³ by x²  in equation (2)

X^(3z) =   (Y^(3))^(3)

X^(3z) =   (X^(2))^(3)

X^(3z) =   X^(6)

3z = 6

divide both-side of the equation by 3

3z/3 = 6/3

On the left-hand side of the equation, 3 at the numerator will cancel-out 3  at the denominator leaving us with just z while on the right-hand side of the equation 6 will be divided by 3

z= 2

What’s greater 5 1/2 or 5 1/4

Answers

Answer:5 1/2

Step-by-step explanation:5 1/2= 5.50

5 1/4= 5.25

5.50>5.25

Answer: I’m pretty sure it’s 5 1/2

Step-by-step explanation:

Daltons dad rode 1 kilometer north 2 kilometers west 1 kilometer south and 2 kilometers east. Dalton rode the same path 5 times . How many kilometers farther did dalton ride?

Answers

Answer:

Dalton didn't ride any kilometer farther since he keeps threading in the same path as that of his father.

Step-by-step explanation:

If Dalton's dad rode 1 kilometer north, 2 kilometers west 1 kilometer south and 2 kilometers east, then he has been moving in a rectangular path.

If Dalton rode in the same path 5times, then Dalton's has not move farther than his dad since he is still moving in the same rectangular path. He is only expending more energy.

Their final destination will still be the same for both of them no matter how many times Dalton keeps threading in the same path.

Answer:

Step-by-step explanation

The formula for the height of a ball as a function of time is given by the equation h = -16t^2 + vt + h, where h is the height of a ball in feet, v is the initial velocity of the ball in feet per second, h is the initial height of the ball in feet, and t is the time in seconds after the ball was thrown.If a ball is thrown from an initial height of 5 feet at an initial velocity of 20 feet per second, what is its height after 1 second?

Answers

It's really poor form to use 'h' to mean two different things in two different
places in the same formula.  Fortunately, we know what you mean.

H = h + vt - 16t²

You have said that ...
initial height = 5 feet
initial velocity = 20 feet per second, no direction given
time = 1 second


Since you gave us the magnitude of the initial velocity but not its direction,
there are a huge number of possibilities.  I'll focus only on two of them: 
20 feet per second straight down, and 20 feet per second straight up.

Initial velocity is downward:
H = (5) + (-20) (1) - 16 (1)²
H = 5 - 20 - 16 = 5 - 36 = 31 feet underground after 1 second

Initial velocity is upward:
H = (5) + (20) (1) - 16 (1)²
H = 5 + 20 - 16 = 25 - 16 = 9 feet above ground after 1 second





How do you solve 8a+a-3=6a-2a-3 step by step

Answers

8a + a - 3 = 6a - 2a - 3

1. Add the a's on both sides:

9a - 3 = 4a - 3

2. Shift 4a to the left and -3 to the right of the equals sign (this changes their signs):

9a - 4a = -3 + 3

3. Simplify:

5a = 0

So a = 0

Applying simple mathematical operations, after isolating 'a' we get the solution o =f the given expression is a = 0.

Using operations like addition, subtraction, multiplication, and division, a mathematical expression is defined as a group of numerical variables and functions.

The given expression is

8a+a-3=6a-2a-3


To solve this equation:

Simplify the like terms,

9a-3 = 4a-3

Add 3 on both sides,

9a = 4a

Isolate a by subtracting 4a on both sides,

5a = 0

Dividing both sides by 5 we get,

a = 0.

Hence,

The solution of the given expression a = 0.

To learn more about the mathematical expression visit:

brainly.com/question/1859113

#SPJ6

PLEASE HELP ME OUT IF YOU CAN

Answers

Answer:

D

Step-by-step explanation: